Gestión administrativa-financiera y su relación con la rentabilidad del comercial “Jostyn”, parroquia San Juan, año 2013 - Bustamante Vidal, Betsy Liliana (2015)
This research is entitled "Administrative and financial management and its relationship to the profitability of the business" Jostyn "parish San Juan, 2013." whose purpose is to analyze the profitability of the business, for diagnosing the problem statement was made, determining their causes and effects, and research solutions through targets with their hypothesis. As the company, administrative and financial management, profitability analysis and how to measure it, the economic evaluation is theoretically based. Using primary source of information that yielded the theory research. The methods used were the inductive, deductive, descriptive, analytical, synthetic and statistical. Raising the descriptive and applied research and literature; this investigative techniques that were the interview the manager of the commercial and a survey of business customers, the results and analysis 75% determined that the care provided is excellent commercial adds; profitability analysis of the commercial "Jostyn" calculated the NPV and IRR, resulting in the net present value is $548443,54 and the internal rate of return of 7%, showing that the commercial "Jostyn" is economically profitable.